Model Fama dan French sebagai Pembentukan Portfolio Saham di Indonesia - Rowland Bismark Fernando Pasaribu (Jurnal Akuntansi dan Bisnis, 2009)
This study examines empirically the Fama and French three factor model of stock returns using Indonesian data over the period 2003-2006. Specifically, it examines the behavior of stock prices, in relation to size (market equity, ME) and book-to-market ratio. The major objective of this study is to provide evidence that would contribute to the effort of explaining the 3FM in an emerging market. Our findings reveal a significant relationship between market, size and book-to-market equity factors and expected stock returns in the Indonesian market. The empirical results confirm that even the Fama and French (1993) three factor model holds for the Indonesian Stock Exchange and more robust than CAPM in non-financial stock, in portfolio level still result bad performance.